2013
DOI: 10.1097/bsd.0b013e318286f635
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Measurement of Lumbar Foramen During Axial Loading Using a Compression Device and Computed Tomography

Abstract: FH, FW, and CSA of the IVF, except for L5/S1, decreased significantly during axial loading. Changes in posterior DH correlated well with the changes in foraminal dimensions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 1 publication
4
32
0
Order By: Relevance
“…Iwata et al [12] used CT imaging to study 12 asymptomatic young volunteers while applying axial loads using a compression device. They found that the in-vivo LIVF dimensions decreased significantly at all levels, but increased at the L5-S1 during the axial loading.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Iwata et al [12] used CT imaging to study 12 asymptomatic young volunteers while applying axial loads using a compression device. They found that the in-vivo LIVF dimensions decreased significantly at all levels, but increased at the L5-S1 during the axial loading.…”
Section: Discussionmentioning
confidence: 99%
“…Further, it should be noted that we reconstructed 3D models of the LIVFs and accurately defined the cross sections of the minimal foramen areas. However, the mid-sagittal plane of the cranio-caudal pedicles (mid-sagittal plane) [1012] or the plane along the middle of the cranio-caudal pedicles (mid-pedicle plane) [24] has been used in the literature to define the narrowest foramen areas (Fig. 7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iwata et al . 26 demonstrated the effects of axial loading on the lumbar foraminal geometry in vivo . Zhong et al .…”
Section: Discussionmentioning
confidence: 99%
“…The lumbar intervertebral foramen includes the adjacent vertebral pedicles superiorly and inferiorly, the postero-inferior margin of the superior vertebral body, the intervertebral disc, and the postero-superior vertebral notch of the inferior vertebral body anteriorly 22 . Many studies have focused on the morphology of intervertebral foramen in vivo and in vitro 20,2326 . The foraminal height was reported as 11–23 mm and the foraminal width as 8–10 mm 4,18,23,25,27 .…”
Section: Introductionmentioning
confidence: 99%